2012
DOI: 10.5539/ijef.v4n6p141
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Institutional Investors on Firms Accounting Flexibility: Evidence from Jordan

Abstract: In this paper the existence of the impact of the institutional investor on the firm's accounting flexibility in generating discretionary accruals was verified. For this purpose balanced data cross-sectional regression model for all 70 th Jordanian manufacturing companies listed at Amman Stock Exchange (ASE) over eleven years from 2000 to 2010 was utilized. In the regression model discretionary working capital accruals (DWCA), proxy for earnings manipulation, was set as the dependant variable. Independent varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The research hypothesis stated that there was a significant relationship between ownership percentage of institutional investors and earnings management of companies and our results indicated that there was a positive and significant relationship between institutional shareholders and earnings management. The results is consistent with research results of Cheng and Reitenga (2009), Hashim and Devi (2008) and Salajeghe et al (2012), but it is on the contrary to the research findings of Abdul Jalil and Abdul Rahman (2010), Alves (2011), Yang et al (2009), Fayoumi et al (2010) and Ramadan (2012).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The research hypothesis stated that there was a significant relationship between ownership percentage of institutional investors and earnings management of companies and our results indicated that there was a positive and significant relationship between institutional shareholders and earnings management. The results is consistent with research results of Cheng and Reitenga (2009), Hashim and Devi (2008) and Salajeghe et al (2012), but it is on the contrary to the research findings of Abdul Jalil and Abdul Rahman (2010), Alves (2011), Yang et al (2009), Fayoumi et al (2010) and Ramadan (2012).…”
supporting
confidence: 88%
“…However, the relationship between financial leverage and discretionary accruals was not observed. Ramadan (2012) in his study investigated the impact of institutional investors on accounting flexibility on some 70 listed firms on the Amman Stock Exchange over the period 2002-2010. In this study, working capital accruals was measured by modified Jones' model as an indicator of corporate accounting flexibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This means that the higher the competence of the apparatus and the higher the technological facilities that support the OPD, the higher the quality of financial reports will increase. The results of this study are in accordance with research conducted by Ramadan [15] which confirms that good quality financial reports will provide dedication to accountability or responsibility for the financial statements made.…”
Section: Apparatus Competence Affects the Quality Of Financial Reports By Utilizing Information Technology As An Intervening Variablesupporting
confidence: 90%
“…As aforementioned, the present critical review of the previous studies the correlation between creative accounting determinants and financial reporting quality in the financial sector to be identified (Ramadan 2017). Along with reviewing relevant research and discussing emerging financial sector difficulties, we also advocated the incorporation of creative accounting determinants into their working culture to find the competitive market advantages and boost productivity (Kovalová and Michalíková 2020).…”
Section: Methodsmentioning
confidence: 94%
“…The banking sector worldwide has been experimenting with a new accounting determinants format in an effort to improve their financial reporting. Motivated by the significance of the implementation of creative accounting determinants in the financial sector, as advocated in various recent studies (Matica (Balaciu) et al (2014); Martin et al 2019;Ramadan 2017). According to the technique outlined above, this paper followed a three-step process.…”
Section: Methodsmentioning
confidence: 99%